2019
DOI: 10.3390/ijms20122904
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine Signaling in Chemotherapy-Induced Neuropathic Pain

Abstract: Chemotherapy-induced peripheral neuropathy (CIPN) is a side effect of chemotherapics such as taxanes, vinca alkaloids, and platinum compounds. In recent years, several reports have indicated the involvement of different molecular mechanisms in CIPN. The pathways described so far are diverse and target various components of the peripheral Nervous System (PNS). Among the contributors to neuropathic pain, inflammation has been indicated as a powerful driver of CIPN. Several pieces of evidence have demonstrated a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
65
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 115 publications
(162 reference statements)
1
65
0
1
Order By: Relevance
“…Methotrexate activated microglia, but no changes in CNS cytokine levels were observed (Seigers et al , ). In contrast, several chemotherapeutic drugs, including methotrexate, cisplatin, oxaliplatin, paclitaxel, and vincristine, elevated peripheral inflammatory cytokines to induce chronic pain (Brandolini et al , ). Elevation of peripheral cytokines may also penetrate the blood–brain barrier to directly act on the CNS, and to activate microglia and astrocytes to secrete further cytokines.…”
Section: Introductionmentioning
confidence: 99%
“…Methotrexate activated microglia, but no changes in CNS cytokine levels were observed (Seigers et al , ). In contrast, several chemotherapeutic drugs, including methotrexate, cisplatin, oxaliplatin, paclitaxel, and vincristine, elevated peripheral inflammatory cytokines to induce chronic pain (Brandolini et al , ). Elevation of peripheral cytokines may also penetrate the blood–brain barrier to directly act on the CNS, and to activate microglia and astrocytes to secrete further cytokines.…”
Section: Introductionmentioning
confidence: 99%
“…interleukin‐1 β (IL‐1 β ), IL‐18, IL‐6 and nitric oxide synthase 2 (NOS2)] and antinociceptive factors [e.g. IL‐1 receptor antagonist (IL‐1RA), IL‐18 binding protein (IL‐18BP) and IL‐10] contributes to the development of neuropathic pain . Moreover, research on chemokines has suggested that their systems (ligands/receptors) are involved in pathological nociceptive processes .…”
Section: Introductionmentioning
confidence: 99%
“…IL-1 receptor antagonist (IL-1RA), IL-18 binding protein (IL-18BP) and IL-10] contributes to the development of neuropathic pain. [6][7][8][9] Moreover, research on chemokines has suggested that their systems (ligands/receptors) are involved in pathological nociceptive processes. [10][11][12] Our recent results indicated that the blockade of some chemokine receptors (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…An increase in the peripheral levels of proinflammatory cytokines, changes in immune signaling pathways and a strong correlation between inflammation and peripheral neuropathy caused by chemotherapy have been observed in numerous studies [102,105,106].…”
Section: Activation Of the Immune System And Neuroinflammationmentioning
confidence: 89%
“…These mediators are able to augment proinflammatory processes and act as sensitizers for nociceptors, thus playing a crucial role in the progression of CIPN. Increased concentrations of cytokines and chemokines in the dorsal root ganglia and spinal cord induce alterations in the Schwann cells of peripheral axons, satellite cells in the dorsal root ganglia, and astrocytes in the spinal cord, which all contribute to CIPN development [102,[106][107][108][109][110][111].…”
Section: Activation Of the Immune System And Neuroinflammationmentioning
confidence: 99%